MODIFICATION OF THE FINANCIAL SECURITY DATABASE IN RUSSIAN INDUSTRIAL ORGANIZATIONS - Ivanova, Oksana; Abrashkin, Mikhail; Grishina, Vera; Zakharenko, Irina (Revista Inclusiones, 2020)
Definition of interconnected compositions in the context of the national and economic security of Russia is one of the constituent positions of strengthening the competitiveness and financial independence of Russian industrial organizations. Verification of the data array information flow is largely a tool base for determining key facts when challenges and threats arise. Therefore, the main goals of the article are building the database and mathematical definition of the relationship among indicators to establish the level of the financial security of Russian industrial enterprises. Dialectical research methods determine the fundamental foundations of the issue under study. The proposed methods for integral evaluation of the financial security reflect individual positions in the system of financial risk evaluation and combine both positive and negative features of the industrial production development. The groups for the financial risk evaluation at industrial organizations have been identified in the article as a result of the multicriteria evaluation and the calculated integral indicator, which became the basis for evaluating the competitiveness and financial sustainability both at the current time and in the forecast future.